ANALISIS PEMELIHARAAN MESIN PRODUKSI DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE PADA CV KUSUMA ARGA MUKTI DI YOGYAKARTA - Refica Yulianti; Erni Widajanti (STKIP Subang, 2026)
CV Kusuma Arga Mukti is a limestone mining and processing company operating six main production machines. Based on 2024 data, the company recorded 67 machine failures with a total downtime of 48.64 hours per year. The current maintenance system relies primarily on corrective maintenance, making it unable to prevent failures in a structured and optimal manner. This study aims to analyze the application of the Reliability Centered Maintenance (RCM) method in production machine maintenance. Quantitative data were collected through direct observation and interviews. The analysis stages include System Work Breakdown Structure (SWBS), Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and maintenance Task Selection. FMEA results indicate that the component with the highest Risk Priority Number (RPN = 294) is the Jaw Crusher body/frame. LTA results show that most failure modes fall under category B (Outage Problem) and category A (Safety Problem). The recommended maintenance tasks consist of Time Directed (TD), Condition Directed (CD), and Finding Failure (FF). The implementation of RCM is expected to transform the company's maintenance approach from reactive to proactive, thereby minimizing downtime and continuously improving machine reliability.